A rare radiotherapy-sensitive primitive neuroectodermal tumor with APC gene amplification in an adult: a case report and literature review. Issue 8 (August 2022) - He, Xin; Song, Shan; Yang, Peidan; Cao, Feng; Li, Weijing; Liang, Ping
Primitive neuroectodermal tumor (PNET) of the lung is rare in adults, and treatment options vary. We herein describe the disease course and follow-up of PNET in an adult. A 27-year-old man was admitted to our hospital because of cough and headache, and whole-exome sequencing revealed positive expression of the EWSR1-FLI1 fusion gene and amplification of the APC gene. Although the patient received multidisciplinary treatment including chemotherapy regimens of etoposide plus cisplatin; focal radiotherapy focusing on the cerebrum, lung, and kidneys; and a subsequent palliative gastrointestinal operation, he eventually died of multiple organ functional failure. His overall survival period was 18 months, and his progression-free survival period was 4 months. During the treatment, the patient showed remarkable sensitivity to radiotherapy. In conclusion, PNET of the lung in adult patients is extremely rare, and the prognosis is very poor. Involvement of a multidisciplinary team in the development of personalized therapeutic strategies is essential. This patient with APC gene amplification showed excellent sensitivity to radiotherapy for intrapulmonary and intracranial lesions, suggesting that APC gene amplification may be related to radiotherapy sensitivity. However, further clinical research is needed.